ANALYSIS OF THE ROLE OF CAPITAL STRUCTURE ON THE RELATIONSHIP BETWEEN THE ECONOMIC PARAMETERS THAT DETERMINE THE VALUE OF MANUFACTURING COMPANIES IN INDONESIA AND THAILAND - Diana Dwi Astuti; Hari Sukarno; Nurhayati; Novi Puspitasari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to examine the influence of external factors that are proxied on: Inflation, Interest Rates, GDP, then internal factors that are proxied in: ROA, Size, Asset Structure, NDTS, INOS, INOP, then Innovative Capital partially on the capital structure and value of manufacturing companies. This study also examines the role of capital structure on the value of companies listed on IDX and SET during 2014-2018. This research using a quantitative approach using purposive sampling method, with the statistical test tool SPSS 26. The sample in this study was 35 companies in IDX and 11 companies in SET. The results showed that external factors affect the capital structure, findings on the internal factors of the IDX show that: ROA and size have an effect on the capital structure. Whereas in SET, internal factors: ROA, asset structure, NDTS affect the capital structure. Findings on the external factors of the IDX show that: Inflation, interest rates have an effect on firm value. Whereas in SET, external factors: inflation, interest rates, GDP have an effect on firm value. The findings on the internal factors of the IDX show that: ROA, Size have an effect on firm value. Whereas in SET, internal factors: ROA, asset structure, NDTS have an effect on firm value. This study found that INOS and INOP did not affect company value, both for IDX and SET companies.